Design of reusable novel membranes based on bacterial cellulose and chitosan for the filtration of copper in wastewaters. (1st August 2018) - Urbina, Leire; Guaresti, Olatz; Requies, Jesús; Gabilondo, Nagore; Eceiza, Arantxa; Corcuera, Maria Angeles; Retegi, Aloña
Graphical abstract: Highlights: Development of in situ and ex situ BC/Ch membranes for Cu removal in wastewaters. Interactions, morphology and mechanical properties depend on the processing route. Highest copper removal capacity for in situ biosynthesized membrane. Easily cleanable and reusable membranes. Abstract: This study has been carried out to design novel, environmentally friendly membranes by in situ and ex situ routes based on bacterial cellulose (BC) as a template for the chitosan (Ch) as functional entity for the elimination of copper in wastewaters. Two routes led to bionanocomposites with different aspect and physico-chemical properties. The mechanical behaviour in wet state, strongly related to crystallinity and water holding capacity, resulted to be very different depending on the preparation route although the Ch content was very similar: 35 and 37 wt% for the in situ and ex situ membranes, respectively. The morphological characterization suggested a better incorporation of the Ch into BC matrix through the in situ route. The cooper removal capacity of these membranes was analyzed and in situ prepared membrane showed the highest values, about 50%, for initial concentrations of 50 and 250 mg L −1 . Moreover the reusability of the membranes was assessed. This is the first time that the whole 3D nano-network BC membrane is used to provide physical integrity for chitosan to develop eco-friendly membranes with potential applications in heavy metal removal.